Off-season litchi cultivation - Tripathi, P C; Karunakaran, G (Indian Horticulture, 2018)
Litchi cultivation has not taken a commercial venture in the Western Ghats.The success of some growers has attracted many enthusiastic farmers totake up litchi cultivation on larger scale. More than 20,000 plants of litchiwere planted in the region during last 7 years. The climatic condition of theregion and farmers’ experience show that litchi can be grown successfullyin this region. Though litchi was introduced in the region long back but dueto limited area and less commercial importance, little research work wasdone on evaluation of suitable varieties, production and plant-protectiontechnologies of litchi cultivation for this region. There is a need to conductmore research on varietal evaluation and production, and protectiontechnologies of litchi to popularize litchi cultivation. Further, tropical varietiesof litchi grown in similar latitude in Thailand and other South Easterncountries may be introduced. Litchi cultivation has a bright future in thisregion due to off-season production. Combined research and developmentalefforts for commercial cultivation of litchi in the region may be helpful incrop diversification and income enhancement of farmers.